Landscape of nuclear transport receptor cargo specificity. Issue 12 (18th December 2017) - Mackmull, Marie‐Therese; Klaus, Bernd; Heinze, Ivonne; Chokkalingam, Manopriya; Beyer, Andreas; Russell, Robert B; Ori, Alessandro; Beck, Martin
Abstract: Nuclear transport receptors (NTRs) recognize localization signals of cargos to facilitate their passage across the central channel of nuclear pore complexes (NPCs). About 30 different NTRs constitute different transport pathways in humans and bind to a multitude of different cargos. The exact cargo spectrum of the majority of NTRs, their specificity and even the extent to which active nucleocytoplasmic transport contributes to protein localization remains understudied because of the transient nature of these interactions and the wide dynamic range of cargo concentrations. To systematically map cargo–NTR relationships in situ, we used proximity ligation coupled to mass spectrometry (BioID). We systematically fused the engineered biotin ligase BirA* to 16 NTRs. We estimate that a considerable fraction of the human proteome is subject to active nuclear transport. We quantified the specificity and redundancy in NTR interactions and identified transport pathways for cargos. We extended the BioID method by the direct identification of biotinylation sites. This approach enabled us to identify interaction interfaces and to discriminate direct versus piggyback transport mechanisms. Data are available via ProteomeXchange with identifier PXD007976. Synopsis: This study provides a comprehensive overview of the nuclear transport receptor (NTR) interactome and quantifies the specificity and redundancy of interactions. The BioID method is extended to directly identify biotinylation sites. NTRs transport functionally related cargos. Multiple members of protein complexes are identified suggesting that they are often transported as fully assembled entities. The direct identification of biotinylated peptides enables mapping of potential interaction sites of NTRs. A statistical framework is introduced that allows quantifying interaction specificity. Abstract : This study provides a comprehensive overview of the nuclear transport receptor (NTR) interactome and quantifies the specificity and redundancy of interactions. The BioID method is extended to directly identify biotinylation sites.